PEDAGOGICAL AND PSYCHOLOGICAL PHENOMENA OF THE DEVELOPMENT OF FUTURE TEACHERS COMMUNICATIVE COMPETENCE - D. Sh. Norgoziyeva; M. Q. Usmonova (Galaxy International Interdisciplinary Research Journal, 2023)
This article discusses the pedagogical and psychological foundations for the development of communicative competence of future teachers, the importance of increasing communicative competence when searching for solutions to professional problems, that is, the level of vocabulary, knowledge, skills and qualifications, factors of the pedagogical situation self-cognitive, emotional, volitional control is described with readiness for effective assessment and activity.